Clinical Presentation, Management, and Outcome of Patients with Incidental Renal Angiomyolipoma in Qatar - Hassan Al-Thani; Ayman El-Menyar; Maryam Al-Sulaiti; Jamela El-Mabrok; Khairi Hajaji; Hesham Elgohary; Ahmed Al-Malki; Abdelhakem Tabeb (Oman Medical Journal, 2014)
Objectives: Our study aimed to analyze the clinical presentation, management, and outcome of renal angiomyolipoma patients incidentally detected upon computed tomography (CT) examination.